Self and "being Human": On Herschel's "Who is Man?” - AN, Ximeng (Journal of Research for Christianity in China (JRCC), 2025)
Human being，the "I", has preciousness, uniqueness, uniqueness, opportunity, contingency and non-finality.Human existence is a series of processes and events.He was both alone and united.He knows reward, gratitude and holiness.The question of who a person is is not really a question.A question means a solution and an answer, but being a person is not a question to be answered and has no answer, but requires action and response.You have to be a man, a man. It's a matter of action.To be a person, to be a person, is to be yourself, which means you have to make choices alone.The choice is not to be someone, but to be alone.When you are alone, you become yourself, you become a person, you become a person.Herschel's "Who is the man?"", in effect, "How do you become a person?".'Who am I?It's really about how to be the self.'Who is the man?It's about being human, not just being a static yes.The "being" (that is, doing) involves making choices, becoming, and acting.'Who is the man?", refers to who a person will be, not yet and will be."Who" is not a reality, but the result of change, behavior and choice.In Herschel, survival is not mere existence and survival.The key form of human being is human existence.The proper subject of the study of man, therefore, is the question of existence, how to deal with the question of existence.Whether we can give form to our existence depends on our understanding of the uniqueness of human existence.There is no guarantee or assurance of a meaningful existence.The challenge is not to yield to mere existence.Existence should be transcended by existence.